NMR study of ring opening reaction of epoxidized natural rubber in presence of potassium hydroxide/isopropanol solution. (May 2017) - Dahham, Omar S.; Hamzah, Rosniza; Bakar, Mohamad Abu; Zulkepli, Nik Noriman; Dahham, Saad S.; Ting, Sam Sung
Abstract: The ring opening reaction of epoxidized natural rubber (ENR-50) in the presence of potassium hydroxide/isopropanol solution was studied using NMR, and it's thermal characteristic was investigated using TG/DTG and DSC. 1 H-NMR showed that 16.9% of epoxide units was ring-opened in treated ENR-50, which was also supported by quantitative FTIR spectroscopy. 13 C-NMR proved the location of alkyl group (isopropyl) in the polymer chain of treated ENR-50. The attachment location of isopropyl occurred at both most (↑) and least (↓) hindered carbons of the epoxide. 2D-NMR was used to identify and scrutinize the triad assignment of treated ENR-50. The TG/DTG results presented three decomposition steps at 190-331, 331-521 and 521–706 °C due to the existence of mixtures of polymer chains i.e. ring-opened and intact epoxide of ENR-50, which also led to increase in Tg of treated ENR-50 at 13.2 °C compared with purified ENR-50 at −17.7 °C.